A tri-lingual dictionary of Emberá-Spanish-English (2022)
eng: Emberá is a Central American Indian Languaje belonging to the Choco grouping. It is Spoken in Panama, Colombia and Ecuador in unequal proportions. This study is based on the Emberá dialect spoken in Panama. Though the statistics vary, the number of native speakers is no more than sixty thousand, in toto. In Panama, the number of speakers is no more than twenty thousand. There are no studies in English on Emberá, and a very few in Spanish. This dictionary is based on information and elicitations from the native speaker Mr. Daniel Castañeda. This is the first attempt at a collection of the basic lexical items of the language, and it is first in English and Spanish. Mr. Castañeda is a bilingual is a bilingual speaker of Spanish and Emberá, with limited fluency in English. All elicitations were done through the medium of Spanish at Georgetown University in Washington D. C. while he was residing in the area. For ease of use the dictionary is multi-directional, i.e. Emberá-Spanish-English and Spanish-Emberá-English. Even though this dialect differs from Chamí dialect, this dictionary can serve as a companion to the grammar of Emberá by D. A. Licht, also published by Lincom Europa.